Cultivating Care and Love for The Environment Through Ecobrick Making - Ratna Purwati; Anida Salsabila; Febyan Cein Claresta; Intan Bestari Putri Suharjo; Nurhamidah Nurhamidah; Shofi Fadilah Azizah (PT. Pusmedia Group Indonesia, 2023)
Schools are the main and strategic place in instilling values or caring attitudes in conditions of recovery from the Covid-19 pandemic. MI An-Nur, Cirebon City, is an Islamic Elementary School or equivalent to an Elementary School, which is located on Jl Kutagara, Pekalipan District, Cirebon City. The poor condition of the trash cans and the lack of availability made students dispose of garbage incorrectly according to the type of waste. The habit of throwing garbage in one place without sorting it based on the type of waste is still not visible from the habits of the students. Therefore it is necessary to cultivate an attitude of care and love for the environment through making ecobricks for students. The purpose of this activity is to introduce and provide training and habituation of ecobricks to students so they care about and love the environment so they know how to process waste and not litter. The method used is Qualitative Research which intends to understand the phenomena experienced by utilizing natural methods. The research was carried out at the MI AN-NUR school, Cirebon City, Jagasatru District, which was carried out for 40 days.Data collection techniques used are in the form of observation, interviews (interviews), and documentation.Primary data in this research, in the form of data from student observations in introducing ecobricks and making ecobricks simultaneously accompanied by the teacher and taking photos as evidence of research implementation. Data analysis techniques in this study are data collection, data presentation, data reduction and conclusion/verification. The results of the evaluation can be concluded that the level of students' understanding regarding training and habituation in making ecobricks to instill an attitude of care and love for the environment is categorized as moderate.